Phosphorylated α-Synuclein Accumulations and Lewy Body-like Pathology Distributed in Parkinson's Disease-Related Brain Areas of Aged Rhesus Monkeys Treated with MPTP. (21st May 2018) - Huang, Baihui; Wu, Shihao; Wang, Zhengbo; Ge, Longjiao; Rizak, Joshua D.; Wu, Jing; Li, Jiali; Xu, Lin; Lv, Longbao; Yin, Yong; Hu, Xintian; Li, Hao
Highlights: Dopaminergic cell loss is inversely correlated with phosphorylated Ser 129 α-syn accumulations. The "LB-like" pathology is identified in MPTP-treated aging monkeys' brain. This study provides new insight into PD pathogenesis on monkeys. Abstract: Phosphorylation of α-synuclein at serine 129 (P-Ser 129 α-syn) is involved in the pathogenesis of Parkinson's disease (PD) and Lewy body (LB) formation. However, there is no clear evidence indicates the quantitative relation of P-Ser 129 α-syn accumulation and dopaminergic cell loss, LBs pathology and the affected brain areas in PD monkeys. Here, pathological changes in the substantia nigra (SN) and PD-related brain areas were measured in aged monkeys treated with 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) utilizing a modeling-recovery-remodeling strategy. Compared to age-matched controls, the MPTP-treated monkeys showed significantly reduced tyrosine hydroxylase (TH)-positive neurons and increased P-Ser 129 α-syn-positive aggregations in the SN. Double-labeling Immunofluorescence found some TH-positive neurons to be co-localized with P-Ser129 α-syn in the SN, suggesting the inverse correlation between P-Ser 129 α-syn aggregations and dopaminergic cell loss in the SN may represent an interactive association related to the progression of the PD symptoms in the model. P-Ser 129 α-syn aggregations or LB-like pathology was also found in the midbrain and the neocortex, specifically in the oculomotor nucleus (CN III), temporal cortex (TC), prefrontal cortex (PFC) and in cells surrounding the third ventricle. Notably, the occipital cortex (OC) was P-Ser 129 α-syn negative. The findings of LB-like pathologies, dopaminergic cell loss and the stability of the PD symptoms in this model suggest that the modeling-recovery-remodeling strategy in aged monkeys may provide a new platform for biomedical investigations into the pathogenesis of PD and potential therapeutic development.